Can Paternity Leave Reduce the Gender Earnings Gap? - Yaya Diallo; Fabian Lange; Laetitia Renée (Institute of Labor Economics (IZA), 2025)
This paper examines the impact of paternity leave on the gender gap in labor market outcomes. Utilizing administrative data from Canadian tax records, we analyze the introduction of Quebec's 2006 paternity leave policy, which offers five weeks of paid leave exclusively to fathers. Using mothers and fathers of children born around the reform, we estimate how the policy impacted labor market outcomes up to 10 years following birth. The reform significantly increased fathers' uptake of parental leave and reduced their earnings immediately after the reform. However, in the medium to long-run, we find that the reform did not impact earnings, employment, or the probability of being employed in a high-wage industry for either parent. We for instance find a 95%-CI for the effect on average female earnings 3-10 years following the reform ranging from -2.2 to +1.7%. Estimates of effects on other outcomes and for males are similarly precise zeros. There is likewise no evidence that the reform changed social norms around care-taking and family responsibilities.
Keywords: J13; J16; 330; paternity leave; gender earnings gap